Aurora Printing and Custom / Ainul Mardhiah Noreffendy ... [et al.] - Noreffendy, Ainul Mardhiah; Azmi, Muhammad Faiz Haikal; Mohd jaffar, Sharifah Shamira; Azmi, Adnin; Roszi, Nuha (2022)
Aurora Printing and Custom offers unlimited designs and can be selected according to the tastes of our customers to provide high satisfaction with our services. Our main strategy and goal in developing this business are to Introduce custom items that can be used as birthday gifts, wedding gifts, door gifts, and couple gifts. We always expect our customers' satisfaction with our services. As our company is listed as a new company in the market, there will be many aspects that we need to consider ensuring that our company can compete healthily with other printing shops. This is so because there are many people involved in the business industry including printing services. Furthermore, nowadays there are many events such as cross¬country activities and even feasts that require gifts to be used as souvenirs. We see this as one of the golden opportunities for us to attract customers to our store. Our business is run by five key employees namely the general manager, administrative manager, marketing manager, operations manager, and finance manager. We all play an important role in this business and ensure this business is fully successful. From our observations, we are targeting a large scope of customers because our store is located in a city that has a high chance of getting customers and attracting their attention to come to our store. In addition, our business location is very strategic as it is close to shopping lots and residential areas. We believe that we can achieve our business goals with the statement of the financial position of our business. With quality services and quality products, we are confident that the good word about our services will spread among customers. We also provide home delivery service according to the customer's choice. We hope that Aurora Printing and Custom can become a well-known printing shop in this area and other areas and be able to provide the best service from time to time. We also believe the demand for printing services can increase every year. Lastly, we are honored to be a benchmark to others interested in starting a business in the services we engage in.